Neoadjuvant chemotherapy for advanced stage endometrial cancer: A systematic review - Allan B. Huang (Elsevier, 2021)
Objective: While primary cytoreductive surgery (PCS) is considered the standard of care for women who present with stage IV endometrial cancer, neoadjuvant chemotherapy (NACT) followed by interval cytoreductive surgery (ICS) has emerged as an alternative treatment strategy. We summarized the literature and compared outcomes of PCS compared to NACT and ICS. Methods: We conducted a systematic search on PubMed, Embase, Web of Science, and Scopus for articles published from January 1, 1990 to December 31, 2020. Key search terms included multiple descriptors of advanced disease status in combination with “endometrial cancer” and “neoadjuvant chemotherapy”. Our review included studies that examined survival and surgical outcomes of patients with stage III or IV endometrial cancer treated with neoadjuvant chemotherapy followed by interval cytoreductive surgery versus those who received primary cytoreductive surgery. We excluded studies examining only patients with leiomyosarcomas, carcinosarcomas, and stromal sarcomas due to the biologic heterogeneity of these malignancies. Results: The nine included studies encompassed 5,844 patients, of which 1,317 (22.5%) received NACT and 4,527 received PCS (77.5%). With the exception of a single study, all were retrospective observational studies or case series. Use of NACT in patients with stage IV EC increased from 16.0% in 2010 to 23.9% in 2015. Five studies analyzed median overall survival and all but one reported no significant difference between NACT + ICS vs. PCS. Optimal cytoreduction (<1 cm of residual disease) rates were similar across both treatment groups in three separate analyses, however pooled data suggest improved rates of optimal cytoreduction for NACT + ICS vs. PCS patients (81.9% vs. 51.5% respectively). Patients receiving NACT experienced significantly shorter hospital admissions and lower operative times compared to PCS counterparts. Conclusions: NACT followed by ICS reduces perioperative morbidity while offering similar overall survival.